Strike Limit Algorithm optimisation: a realistic example - H. Givens, Geof (J. Cetacean Res. Manage., 2000)
This paper illustrates a process for finding an improved variant of an aboriginal whaling management procedure Strike Limit Algorithm (SLA), applying the merging and optimisation approach of Givens (1997; 1999b). A modified version of the SLA developed by Punt and Butterworth (1997) was chosen as the procedure to be optimised for management of the Bering-Chukchi-Beaufort Seas stock of bowhead whales. The optimisation considers functions of the catch limit and other outputs from the nominal SLA, along with outputs from two other SLAs and estimates of certain population dynamics parameters. The result reduced the Bayes risk by over 90%, compared to the nominal procedure, and improved simulated SLA performance by usually allowing more strikes at less depletion risk. Such results suggest that this approach may be attractive in the general development of wildlife management procedures.